Methodological Concept for User Experience Research of Interfaces Based on Norman’s Model - Jarosz, Kornel (Koncepcja procedury metodycznej dla badań doświadczeń użytkowników z wykorzystaniem modelu Normana, 2024)
Aim: The article aims to present a methodological procedure, and tools designed to enable a detailed and systematic analysis of user experience (UX) and user interface (UI) in a selected software solution, using a model based on Norman’s design concepts. Methodology: A literature review was conducted, analysing methods for evaluating user experience and Don Norman's design concept. This review identified Norman’s model, developed to evaluate the ePortal platform interface, which served as the foundation for proposing a systematic approach to UX/UI analysis. The approach includes seven stages: compiling a list of interface elements based on the literature, selecting software solutions for analysis, identifying and evaluating interface elements, conducting a comparative analysis, and formulating design recommendations and guidelines. Results: The proposed methodology led to the creation of structured tables that support the systematic evaluation of user interfaces based on Norman’s model. These tables enable the identification, assessment, and comparative analysis of interface elements across the visceral, behavioural, and reflective levels. They provide a basis for generating design recommendations and practical guidelines tailored to the analysed solutions. Implications and recommendations: The proposed methodology integrates theoretical foundations with practical application, facilitating the identification of usability issues and the formulation of actionable design recommendations. While the initial implementation may be time-intensive due to the need for detailed interface documentation, subsequent iterations become more efficient. Future empirical studies are recommended to validate the methodology’s effectiveness in various digital contexts, such as mobile applications, educational platforms, and e-commerce systems. Originality/value: This article contributes by introducing a structured procedure for evaluating user interfaces based on Norman’s design principles. It addresses gaps in the literature by combining robust theoretical underpinnings with practical tools. A notable innovation is the introduction of dedicated tables to guide each phase of the analysis. These tables streamline the evaluation process, document findings, and facilitate the development of comprehensive design recommendations.
Business Informatics = Informatyka Ekonomiczna, 2024, Nr 1-2 (67-68), s. 36-44
Keywords: user experience; user interface; Norman's model; evaluation; heuristics; model Normana; ocena; heurystyki